2022
DOI: 10.1111/birt.12623
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of mental health interventions during and after pregnancy: A systematic review

Abstract: Background Mental health problems during and after pregnancy such as depression, anxiety, post‐traumatic stress disorder (PTSD), or addiction are common and can have lifelong implications for both parents and offspring. This review investigates the cost‐effectiveness of interventions tackling these problems, assesses the methodological quality of included studies, and indicates suggestions for further research. Methods Thirteen databases were searched for economic evaluations of interventions related to antena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…A recent systematic review identified that a relatively low number of studies have investigated the cost-effectiveness of interventions tackling mental health problems during and after pregnancy (Verbeke, et al, 2022). The healthcare utilization and costs associated with perinatal depressive symptoms have been found to be significant (Bauer et al, 2016(Bauer et al, , 2022Luca et al, 2020;Pollack et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review identified that a relatively low number of studies have investigated the cost-effectiveness of interventions tackling mental health problems during and after pregnancy (Verbeke, et al, 2022). The healthcare utilization and costs associated with perinatal depressive symptoms have been found to be significant (Bauer et al, 2016(Bauer et al, , 2022Luca et al, 2020;Pollack et al, 2022).…”
Section: Introductionmentioning
confidence: 99%